2015
DOI: 10.1088/1757-899x/96/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

Earth's Surface Displacements from the GPS Time Series

Abstract: Abstract. The GPS observations of both Latvian permanent GNSS networks -EUPOS® -Riga and LatPos, have been collected for a period of 8 years -from 2007 to 2014. Local surface displacements have been derived from the obtained coordinate time series eliminating different impact sources. The Bernese software is used for data processing. The EUREF Permanent Network (EPN) stations in the surroundings of Latvia are selected as fiducial stations. The results have shown a positive tendency of vertical displacements in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Modern data obtained in 2015 showed that the velocities of the vertical movements of the permanent GNSS stations of LatPos network (Fig. 1) are + 0.52 mm/year for Lielvarde (LVRD) and + 0.30 mm/year for Lode (LODE) (Haritonova et al, 2015). The LODE station is located in the center of the Vidzeme Upland, and LVRD is located about 30 km to the south-west of the edge of the Vidzeme Upland.…”
Section: Discussionmentioning
confidence: 99%
“…Modern data obtained in 2015 showed that the velocities of the vertical movements of the permanent GNSS stations of LatPos network (Fig. 1) are + 0.52 mm/year for Lielvarde (LVRD) and + 0.30 mm/year for Lode (LODE) (Haritonova et al, 2015). The LODE station is located in the center of the Vidzeme Upland, and LVRD is located about 30 km to the south-west of the edge of the Vidzeme Upland.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, indirect methods are applied (Borowski and Banasik, 2011). Although the ellipsoidal heights of stations change over time (Haritonova et al, 2015;Maciuk and Szombara, 2018), the undulation values are considered relatively constant (Banasik, 1999;Czarnecki, 2010)…”
Section: Examination Of the Geoidmentioning
confidence: 99%